Aplicación de un portal web con lenguaje actualizado para la administración y gestión de la red escolar autónoma rural de centros educativos comunitarios Interculturales Bilingües “La Cocha” ubicada en la provincia de Cotopaxi, en la ciudad de Latacunga en el período 2011-2012 - Chimbo Chancusi, Patricia Aracely (2013)
The present research we put in consideration is: application of a portal web with updated language for administration and management of the autonomous community learning centre rural bilingual intercultural “La Cocha” school network, by applying a methodology engineering web. This portal was conducted in compliance with all required parameters according to the proposed topic. Ruby on Rails is an opened, interpreted, flexible, object-oriented source language, which is based on patterns, views and controllers that allow dynamic and robust applications, enabling the creation of web interfaces with advanced and personalized design. The web portal has been developed with all the elements and components necessary for the user comfort, in a friendly environment for navigation in the system. With the web portal implementation has been providing management, centralizing administrative and management processes with the latest technology. The users do not have the need to travel longer to the Central Office located in Latacunga city, since they can access the Portal Web from any device with internet access to communicate with management directly, keep abreast of interest news, access by your user account to manage your information. Within the web portal users can find a portfolio which has its respective payroll, personal data, courses taken, work history, published works, resume, personal control them that is stored in the database . With the research conducted to test the hypothesis was achieved and improve the information system with teachers on “La Cocha” School Net.